Coupling effect of suction variation on riverbank stability - Foroutan, Maziar (2013)
Failure of riverbank slope is a common problem in tropical country like Malaysia. Problems are often encountered when calculating the real factor safety of riverbank slope due to varying rainfall intensity and fluctuating of surface water table applied on the slope. In this study, the coupling effect of rainfall infiltration and tidal cycle on riverbank stability was investigated by measuring suction development in the riverbank slope. The coupling effect of suction variation on riverbank stability becomes more complicated as the up going tide of water on the riverbank saturates the soil mass resulting in negative effect to the Factor Safety, and on the contrary, the weight of surface water applied on the face of riverbank contributes to positive Factor of Safety. Furthermore, the riverbank slope failure induced by rainfall, involves infiltration through unsaturated zone above ground water table. Therefore, to achieve stability analysis in term of rainfall effect, the slope should be considered as an integral system of saturated- unsaturated soils. The critical factor of safety on the riverbank slope was calculated by integrating simulated pore water distribution in the slope by using SEEP/W into SLOPE/W software. From monitoring factor of safety it was found that the coupling effect of extraordinary rainfall, which makes the soil over-saturated and ponds on the slope, and tidal effect induces failure on the riverbank slope